Ekstrak daun kemangi (ocimum basilicum linn) terhadap perubahan warna elemen gigi tiruan - Karunia Ramadhani, Alifia; Adrian, Nova (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: Denture elements are parts that are used to replace missing teeth in removable partial dentures. The color of the tooth element is one of the important things because it is related to aesthetics. Apart from being used as an ingredient in cooking, basil leaves are also known to have antibacterial and antimicrobial effects. Purpose: This study aims to determine the effect of immersion time of basil leaf extract on changes in the color of acrylic denture elements. Methods: In this study, Ortolux brand acrylic resin denture elements with A3 color were used. The study was conducted by immersing denture elements in aquadest and basil leaf extract, then divided into a treatment group and a control group. In the treatment group, 20 mL of basil leaf extract was added and 20 mL of aquadest was added to the control group. Color measurement was carried out using a VITA easyshade V type spectrophotometer at the initial time before immersion and then at the 35 and 70 minutes. Calculation of the data using the normality test with the Shapiro-Wilk method, then continue with the independent T test and the Mann-Whitney test. Results: The results obtained from this study showed a significant change in E and C, but there was no significant color change in L and H. Conclusion: The use of basil leaf extract as a denture cleaning agent has a discoloration effect on acrylic resin denture elements.